The Questioning Techniques of Primary School Mathematics Teachers in their Journey to Incorporate Dialogic Teaching - Rosni Othman; Masitah Shahrill; Roslinawati Roslan; Farida Nurhasanah; Nordiana Zakir; Daniel Asamoah (SEAMEO Regional Centre for QITEP in Mathematics, 2022)
Questioning is one of the critical repertoires in dialogic teaching. Teachers who set dialogic classrooms need to be able to use questioning effectively. Effective questioning techniques by teachers improve teacher-student instructional dialogues in primary school mathematics classrooms. In this study, the questioning practices of three primary school mathematics teachers were analysed in their journey to incorporate dialogic teaching. Data were gathered through lesson observations, video recordings and teacher interviews. The three teachers’ classroom discourses were transcribed verbatim, and teachers’ questions were analysed to find out the types of questions, how the teachers asked the questions and the feedback given to the student’s responses. Findings from this study indicated that the three teachers used effective questioning techniques in ensuring dialogic teaching, with focusing, genuine enquiry, and closed testing questions being the most predominant. The teachers portrayed positive attitudes towards dialogic teaching and shared their comprehensive understanding of the approach.